2013
DOI: 10.1126/scitranslmed.3005964
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Mononuclear Cell Gene Expression Profiles Predict Poor Outcome in Idiopathic Pulmonary Fibrosis

Abstract: We aimed to identify peripheral blood mononuclear cell (PBMC) gene expression profiles predictive of poor outcomes in idiopathic pulmonary fibrosis (IPF) by performing microarray experiments of PBMCs in discovery and replication cohorts of IPF patients. Microarray analyses identified 52 genes associated with transplant-free survival (TFS) in the discovery cohort. Clustering the microarray samples of the replication cohort using the 52-gene outcome-predictive signature distinguished two patient groups with sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
241
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 268 publications
(266 citation statements)
references
References 44 publications
(48 reference statements)
16
241
1
Order By: Relevance
“…Thus, there are numerous biological precedents that could plausibly explain the development of autoimmunity in IPF as a secondary consequence of another, distinctly different lung injury(ies) that actually triggers the disease. Nonetheless, at least some of the many autoimmune responses that have been discovered in IPF patients, in addition to the antivimentin in this study, seem to play important roles in disease severity and progression (2,(4)(5)(6)(7)(8)(9)(10)(13)(14)(15)(16). In addition, pathogenic secondary immune responses could cause or contribute to the well-known resistance of IPF to conventional therapies, because many other autoantibody-mediated lung diseases are similarly refractory to nonspecific agents, including glucocorticoids (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there are numerous biological precedents that could plausibly explain the development of autoimmunity in IPF as a secondary consequence of another, distinctly different lung injury(ies) that actually triggers the disease. Nonetheless, at least some of the many autoimmune responses that have been discovered in IPF patients, in addition to the antivimentin in this study, seem to play important roles in disease severity and progression (2,(4)(5)(6)(7)(8)(9)(10)(13)(14)(15)(16). In addition, pathogenic secondary immune responses could cause or contribute to the well-known resistance of IPF to conventional therapies, because many other autoantibody-mediated lung diseases are similarly refractory to nonspecific agents, including glucocorticoids (8).…”
Section: Discussionmentioning
confidence: 99%
“…T cell-related genes and proteins, such as CD28 and LCK, have been identified as prognostic biomarkers in IPF (13,16). Furthermore, T cell depletion attenuates fibroblast proliferation and extracellular matrix (ECM) accumulation in experimental models of pulmonary fibrosis (17).…”
mentioning
confidence: 99%
“…A gene expression analysis of peripheral blood mononuclear cells in patients with IPF using an RNA microarray platform identifi ed several diff erentially expressed genes, including CTLA-4 , ICOS , and CD28 , within the T-cell biocarta pathway. 34 Reduced expression of each of these genes was associated with an increased hazard of death in two IPF cohorts. Genes encoding CTLA-4 , ICOS , and CD28 lie within 300kb on the long arm of chromosome 2, and polymorphisms at this locus have been linked previously to autoimmune thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…103 These findings were supported further by genomic analysis of peripheral blood mononuclear cells from two separate IPF cohorts that showed that low expression of four genes, LCK, ITK, ICOS, and CD28, was associated with increased IPF mortality. 104 These four genes all map to the T-cell costimulatory signal pathway and suggest that repeated cycles of T-cell stimulation are associated with the development of a pathologic T-cell phenotype and a significantly worsened prognosis in IPF. 103 …”
Section: T-cells: Sema7a and Cd28mentioning
confidence: 99%
“…Newer studies will likely focus on the data that are obtainable from peripheral blood mononuclear cells. 104 Another potential source of information may be the isolation of circulating microRNA species. 122,123 How should biomarkers be studied?…”
Section: Future Directionsmentioning
confidence: 99%